Influence of strain-rate related parameters on the simulation of ballistic impact in woven composites. (15th November 2022) - Ma, Dayou; Wang, Zhen; Giglio, Marco; Campos Amico, Sandro; Manes, Andrea
Abstract: The mechanical behaviour of strain-rate-dependent materials varies when they are exposed to dynamic conditions (compared with static ones), and material parameters like modulus, strength, and failure strain may depend on the loading rate. Simulation of the ballistic impact effect on composite materials may be strongly dependant on the suitable calibration of the strain rate effect on their constitutive law. Indeed, knowledge of the strain rate-dependent properties is of great interest but still lacks comprehensive studies (i.e., the effect on the mechanical parameters, besides strength, is commonly ignored). In the present work, three meso-heterogeneous models for 2D woven glass-fibre composites under impact loading were built considering strain rate-dependent strength, modulus and failure strain, coupled with macro-homogeneous models with and without the strain rate effect on strength. All the numerical predictions were compared with actual ballistic test results. It was found that the accuracy in residual velocity and damage morphology predictions can be improved by considering the strain rate effect on modulus and failure strain.